In vitro response and effect of gamma irradiation on four local indica rice varieties - Islam, Md. Monirul; Rahman, Md Taufiqur; Hasanuzzaman, Md.; Islam, Md. Shahidul; Uddin, Md. Imtiaz; Saha, Nihar Ranjan (Journal of Scientific Agriculture, 2020)
In vitro response of four local Indica rice cultivars viz. Sadamota, Kachamota, Moulata and Dudhkalam was evaluated. The aim of this study is to develop an efficient protocol for callus induction, plant regeneration and to observe the effect of gamma radiation on plant regeneration for creating possible genetic variability. In Different concentration of 2,4-D and growth regulators were supplemented with MS medium (Murashige and Skoog’s) to observe their callus induction frequency using mature embryo as explant. Among the cutivars, the highest primary callus (92.55%) as well as embryogenic callus induction (56.26%) was showed in sadamota at 3.0 mgl-1 2,4-D and 10 mgl-1 kinetin under dark condition. Twenty one days old embryogenic calli were exposed to 0, 2, 4 and 6 Gy of gamma rays and transferred to regeneration medium. Both callus growth and regeneration capacity were found to be decreased with increasing level of exposure to gamma rays. The doses of 4 Gy of gamma radiation were found to be the 50% inhibition dose for callus growth and plant regeneration in sadamota and kachamota, repectively whereas the 50% inhibition dose for moulata and dudhkalam at 2 Gy. This results indicate that sentivity of gamma radiation on rice callus depends on genotype of a genus.